Integral #2

Calculus Level pending

1 1 x 2 3 x 2 + 2 x + 5 d x = a + ln ( b ) + c π \int_1^{-1} \frac{x^{2} - 3}{x^2 + 2x + 5}\ dx = a + \ln(b) + c\pi

The equation above holds true for rational numbers a a , b b , and c c . What is a + b + c a+b+c ?


The answer is 0.75.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
Mar 24, 2020

I = 1 1 x 2 3 x 2 + 2 x + 5 d x = 1 1 x 2 3 ( x + 1 ) 2 + 4 d x Let x = u 1 d x = d u = 0 2 u 2 2 u 2 u 2 + 4 d u = 0 2 u 2 + 4 2 u 6 u 2 + 4 d u = 0 2 d u + 0 2 2 u u 2 + 4 d u + 6 4 0 2 1 u 2 4 + 1 d u Let t = u 2 d t = d u 2 = u + ln ( u 2 + 4 ) 0 2 + 3 0 1 1 t 2 + 1 d t = 2 + 0 + ln 8 ln 4 + 3 tan 1 t 0 1 = 2 + ln 2 + 3 4 π \begin{aligned} I & = \int_1^{-1} \frac {x^2-3}{x^2+2x+5} dx \\ & = - \int_{-1}^1 \frac {x^2-3}{(x+1)^2+4} dx & \small \blue{\text{Let }x = u-1 \implies dx = du} \\ & = - \int_0^2 \frac {u^2 - 2u -2}{u^2 + 4} du \\ & = - \int_0^2 \frac {u^2 + 4 - 2u -6}{u^2 + 4} du \\ & = - \int_0^2 du + \int_0^2 \frac {2u}{u^2 + 4} du + \blue{\frac 64 \int_0^2 \frac 1{\frac {u^2}4+1} du} & \small \blue{\text{Let }t = \frac u2 \implies dt = \frac {du}2} \\ & = -u \ + \ln (u^2+4)\ \bigg|_0^2 + \blue{3 \int_0^1 \frac 1{t^2+1} dt} \\ & = -2+0 + \ln 8 - \ln 4 + 3 \tan^{-1} t \ \bigg|_0^1 \\ & = -2 + \ln 2 + \frac 34 \pi \end{aligned}

Therefore a + b + c = 2 + 2 + 3 4 = 3 4 = 0.75 a+b+c = -2+2 + \frac 34 = \frac 34 = \boxed{0.75} .

1 1 x 2 3 x 2 + 2 x + 5 d x = 1 1 x 2 3 x 2 + 2 x + 5 d x = 1 1 ( 1 + 2 x + 8 x 2 + 2 x + 5 ) d x = 1 1 ( 1 + 2 ( x + 1 ) ( x + 1 ) 2 + 4 + 6 ( x + 1 ) 2 + 4 ) d x = [ x + ln ( ( x + 1 ) 2 + 4 ) + 3 tan 1 ( x + 1 2 ) ] 1 1 = 1 + ln ( 8 ) + 3 tan 1 ( 1 ) ln ( 4 ) 1 \int_{1}^{-1}\frac{x^{2} - 3}{x^{2} + 2x + 5}dx = -\int_{-1}^{1}\frac{x^{2} - 3}{x^{2} + 2x + 5}dx = \int_{-1}^{1} (-1 + \frac{2x + 8}{x^{2} + 2x + 5})dx = \int_{-1}^{1} (-1 + \frac{2(x + 1)}{(x + 1)^{2} + 4} + \frac{6}{(x + 1)^{2} + 4})dx = [ -x + \ln((x+ 1)^{2} + 4) + 3\tan^{-1}(\frac{x + 1}{2}) ]_{-1}^{1} = -1 + \ln(8) + 3\tan^{-1}(1) - \ln(4) - 1

Upon simplification:

1 1 x 2 3 x 2 + 2 x + 5 d x = 2 + ln ( 2 ) + 3 π 4 \int_{1}^{-1}\frac{x^{2} - 3}{x^{2} + 2x + 5}dx = -2 + \ln(2) + \frac{3\pi}{4}

Thus, a = 2 , b = 2 , c = 3 4 a = -2, b = 2, c = \frac{3}{4} . a + b + c = 3 4 a + b + c = \boxed{\frac{3}{4}}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...